2014
DOI: 10.1002/dc.23137
|View full text |Cite
|
Sign up to set email alerts
|

Needle tract seeding: An avoidable complication

Abstract: Needle tract seeding refers to implantation of tumor cells by contamination when instruments like biopsy needles are used to examine, excise or ablate a tumor. Implantation along needle tract may lead to change of stage of the tumor, converting a resectable tumor into an inoperable one. In this paper we have reviewed the cases of needle tract seeding due to fine needle aspiration cytology (FNAC) procedure. We analyzed the various aspects of needle tract seedling and suggested how to take precautionary measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 43 publications
1
33
1
1
Order By: Relevance
“…Percutaneous sampling remains a common method to obtain sample where endoluminal ultrasound techniques are not available. Apart from immediate complications related to visceral injury and bleeding, one of the most important late complications is needle tract seeding [1]. Needle tract seeding refers to implantation of tumor cells by contamination when instruments like biopsy needles are used to examine, excise or ablate a tumor [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous sampling remains a common method to obtain sample where endoluminal ultrasound techniques are not available. Apart from immediate complications related to visceral injury and bleeding, one of the most important late complications is needle tract seeding [1]. Needle tract seeding refers to implantation of tumor cells by contamination when instruments like biopsy needles are used to examine, excise or ablate a tumor [2].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatobiliary malignancies form a prime example of such tumors. The occurrence of needle tract seeding is well recognized complication of percutaneous techniques of obtaining tissues from such lesions [1]. Here we present an interesting and rare case of needle tract seeding of colonic malignancy presenting with polypoidal soft tissue mass.…”
Section: Introductionmentioning
confidence: 90%
“…It is reported that macrophages repolarize from an M1 type toward tumor promoting M2 type after a tumor biopsy might accelerate tumor progression [9]. Several studies suggest that FNA can rarely cause needle track seeding or cutaneous metastasis at Biopsy Site in renal, pancreatic and hepatic (primary or metastatic) cancers [9][10][11]. As well, a few cases of breast cancer with the same complication after CNB have been reported [12,13].…”
Section: Surgical Biopsymentioning
confidence: 99%
“…However, it is rational to suppose that biopsy increases the rate of local recurrence, which could be related to the width of biopsy tract and adequacy of hemostasis (4). Biopsy tissue can be obtained through a core-needle biopsy, an incisional biopsy or an excisional biopsy and biopsy cells can be obtained through fine needle aspiration (4). The purpose of this paper was to review the current concepts in biopsy of musculoskeletal tumors.…”
Section: Contextmentioning
confidence: 99%